The Correlation Between Self-Efficacy And English Achievement At Eleventh Grade Of MAN 2 Padang Panjang - Maslinda Jasra; Syahrul Syahrul; Veni Roza; Genta Sakti (Al-Afkar: Jurnal Pemikiran dan Pendidikan Islam, 2026)
This research aims to determine the correlation between Self efficacy and English achievement at eleventh grade of MAN 2 Padang Panjang. Most of the students’ there still encounter problems in mastering English achievement. Some students’ English achievement were not satisfying yet, it was supported by the score of English test result. There were some of students had high Self efficacy in learning English. They felt confident and able to handle a task given by the teacher. However, their English achievement were still low from standardization of minimum criteria. It means some of them have high self efficacy but low in English achievement. Then the researcher was interested in doing research about The Correlation between Self Efficacy and English Achievement. This research used correlational reseach. The total population was 310 students, the sample was taken from 49 students who divided into two classes of XI IPS 1 and XI IPS 2. Data obtained through a questionnaire about self efficacy that researcher distributed to students, while the students’ English achievement was collected from the English teacher’ document. Furthermore, the data collected will be processed using Pearson product moment formula and SPSS program. To test the hypothesis, researchers used the r-test and consulted the results with a t-table with ɑ = 0.05. Based on the result of the research, the correlation coefficient (rxy) between self efficacy and English achievement was 0.655. It means there was a positive direction between two variables. Then, the correlation between Self efficacy and English achievement is in the enough category. This can be seen from the calculated r value of 0.655 which is in the range of 0.40 – 0.70 with a enough category. In addition to test hypothesis, r-test is 0.655, while the r-table on df = 47 and ɑ = 0.05 is 0.288. It means that the r-test was bigger than the r-table. In other words, Ha is accepted, which states that there is a significant correlation between students’ Self efficacy and their English achievement at eleventh grade of MAN 2 Padang Panjang.